Diatom and coccolithophore species fluxes in the Subtropical Frontal Zone, east of New Zealand. (March 2021) - Wilks, Jessica V.; Nodder, Scott D.; Rigual-Hernández, Andrés
Abstract: The Chatham Rise supports some of New Zealand's most economically valuable commercial fish stocks, fuelled by the highly productive waters of the Subtropical Frontal Zone (STFZ). Climate change-related shifts in phytoplankton community structure and function are predicted and may affect Chatham Rise productivity and deep-sea carbon sequestration by the biological carbon pump. However, little is known about how two major phytoplankton groups, diatoms and coccolithophores, will respond, since the seasonality of their productivity and export fluxes to the seafloor are not well known in the SW Pacific sector. This study is the first to report on the seasonal cycle of phytoplankton species fluxes in the STFZ, using a 12-month sediment trap record (1996–1997) on the northern (subtropical-influenced) and southern (subantarctic-influenced) flanks of the Chatham Rise. Diatom and coccolith flux assemblages were characterised and compared with biogeochemical fluxes from the same sites over the same time-frame. Northern phytoplankton flux composition was typical of the subtropics, with most particulate organic carbon (POC) and biogenic silica export associated with diatom fluxes. Fluxes to the northern trap were largely composed of coastal and benthic diatom taxa, reinforcing previous interpretations suggesting lateral advection and sediment resuspension along and across the Chatham Rise slope, influenced also by the Wairarapa Eddy. At the southern site, phytoplankton fluxes were on average an order of magnitude higher than at the northern site and comprised a combination of subantarctic and frontal zone diatom taxa. The majority of the annual diatom flux in the southern trap occurred during a spring Pseudo-nitzschia "pulse" associated with high biogenic silica and POC fluxes, which are inferred to be from subsurface chlorophyll maxima. High coccolith flux at the southern STFZ site was consistent with ecosystem processes observed from other subantarctic export regimes. Phytoplankton successions inferred from the sediment trap records suggest that coccolithophores precede diatoms in spring, which is contrary to expectations from classical studies where the opposite temporal trend is suggested. While maximum diatom species flux co-occurred with peak POC flux at both sites in spring, the estimated contribution of organic carbon associated with diatoms to POC flux was negligible (<0.05%). Estimated coccolithophore POC flux was also low, suggesting that either other phytoplankton groups and/or zooplankton-mediated processes (e.g. fecal pellet fluxes) must contribute more substantially to POC export in the STFZ. Our findings provide new insights into phytoplankton export flux pathways to the seafloor in the Chatham Rise region, with implications for regional biogeochemistry, paleoceanographic and export modelling studies. Highlights: The first annual report of diatom and coccolithophore species flux is provided. Diatom and coccolith fluxes were significantly greater in the subantarctic trap than the subtropical trap. Subtropical diatom fluxes comprised a significant coastal input. Subantarctic diatom fluxes were dominated by a Pseudo-nitzschia pulse event. Seasonal progression from coccolithophores to diatoms was observed during spring-summer.